Comparative Study of Banks in The Perspective of Syafruddin Prawiranegara and M. Syafii Antonio - Muhammad Amin Azis; Muhsin Hariyanto (Universitas Muhammadiyah Yogyakarta, 2021)
The Law of Bank Interest is a complicated issue in Islamic economics because there are differences of opinion among Muslim scholars and intellectuals. This can not be separated from the observations of Indonesian Muslim economists such as Syafruddin Prawiranegara, who thinks bank interest is permissible, while M. Syafii Antonio believes bank interest is haram (forbidden in Islam). This research is entitled